A Comparison of Early Clinical and Radiographic Complications of Iliac Screw Fixation Versus S2 Alar Iliac (S2AI) Fixation in the Adult and Pediatric Populations. Issue 4 (May 2015) - Ilyas, Haariss; Place, Howard; Puryear, Aki
Abstract : Study Design: Retrospective chart review. Objective: To compare short-term clinical and radiographic complications between iliac screw (IS) and S2 alar-iliac (S2AI) screw fixation techniques in the adult and pediatric populations. Summary of Background Data: Pelvic fixation with lumbosacral implants is in widespread practice with numerous indications. Several techniques for spinopelvic fixation have been described in the literature. Although the iliac screw technique is widely practiced, it presents several challenges, including the use of connectors, more lateral surgical dissection, and some complaints of pain over the posterior pelvis. The S2AI method has recently been proposed as an alternative technique that minimizes these complications. Methods: We retrospectively reviewed the charts of 65 adult patients (43 IS, 22 S2AI) and 55 pediatric patients (40 IS/unit rod, 15 S2AI) in a consecutive series who underwent spinopelvic fixation. Acute, spinopelvic implant-related, and delayed complications, including persistent pain over the gluteal region occurring longer than 3 months postoperatively, were recorded from both clinical and radiographic encounters. Statistical analyses were performed among the adult and pediatric group, respectively, as well as a pooled cohort. Results: The adult cohort found an 18.6% absolute risk reduction (ARR) in implant loosening ( P =0.029) and a 21.1% ARR ( P =0.05) in late pain with the S2AI method. In the pediatric population, the S2AI method demonstrated a 22.2% ARR ( P =0.049) in both occurrence of revision surgery secondary to spinopelvic implant failure and late pain. In the pooled cohort, the S2AI method had a 13% ARR ( P =0.033) in acute infections, 18.1% ARR ( P =0.003) in implant loosening, 14.5% ARR ( P =0.009) in revision surgery, 18.7% ARR ( P =0.015) in late pain, and a 10.8% ARR ( P =0.031) in delayed wound issues. Conclusions: The S2AI technique is associated with significantly less clinical and radiographic complications in both the pediatric and adult populations when compared with the iliac screws technique. Level of Evidence: Level III.